ANALISIS EFEKTIVITAS, KONTRIBUSI, DAN POTENSI PENERIMAAN PAJAK PARKIR DI KABUPATEN BANYUWANGI - Wicaksono, Galih; Puspita, Yeni (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- This study aims to determine the level of effectiveness, contributions, and potential of parking tax revenues in the Banyuwangi Regency.Design/methodology/approach- The research method uses quantitative descriptive, which is in the form of an explanation of the results of calculations related to the effectiveness, contributions, and potential parking tax revenue. Findings- This research results in finding that for effectiveness at 87.80% it is in the quite effective category, a contribution of 0.65% in the criteria is very less. For potential, it resulted in a finding of Rp 1,049,932,800, which is above the realization of only Rp790,236,000, or in other words that the realization of parking tax revenues is only 75.26% of the potential revenue in the three districts.Implications-The results of this study concluded that the potential for parking tax revenues obtained from three districts is greater than the total realization of parking tax revenues in the Banyuwangi Regency. Therefore, the Banyuwangi Regency Government needs to find the right strategy in maximizing the potential of parking tax revenues, as well as finding the right formula in increasing the effectiveness and contribution of parking tax revenues to local taxes. Keywords: Parking Tax, Effectiveness, Contribution, Potential